Genetic Association and Expression Correlation between Colony-Stimulating Factor 1 Gene Encoding M-CSF and Adult-Onset Still's Disease. (14th February 2020) - Chen, Yi-Ming; Hung, Wei-Ting; Chang, Wan-Chun; Hsieh, Chia-Wei; Chung, Wen-Hung; Lan, Joung-Liang; Gung, Ning-Rong; Lee, Yun-Shien; Chen, Der-Yuan; Hung, Shuen-Iu
Abstract : Adult-onset Still's disease (AOSD) is a rare and inflammatory disorder characterized by spiking fever, rash, arthritis, and multisystemic involvement. HLA has been shown to be associated with AOSD; however, it could not explain the innate immunity and autoinflammatory characteristics of AOSD. To assess the genetic susceptibility of AOSD, we conducted a genome-wide association study (GWAS) on a cohort of 70 AOSD cases and 688 controls following a replication study of 36 cases and 200 controls and meta-analysis. The plasma concentrations of associated gene product were determined. The GWAS, replication, and combined sample analysis confirmed that SNP rs11102024 on 5 ′ -upstream of CSF1 encoding macrophage colony-stimulating factor (M-CSF) was associated with AOSD (P = 1.20 × 10 -8, OR (95% CI): 3.28 (2.25 4.79)). Plasma levels of M-CSF increased in AOSD patients (n = 82, median: 9.31 pg/mL), particularly in the cases with activity score ≥ 6 (n = 42, 10.94 pg/mL), compared to the healthy donors (n = 68, 5.31 pg/mL) (P < 0.0001 ). Patients carrying rs11102024TT genotype had higher M-CSF levels (median: 20.28 pg/mL) than those with AA genotype (6.82 pg/mL) (P < 0.0001 ) or AT genotype (11.61 pg/mL) (P = 0.027 ). Patients with systemic pattern outcome were associated with elevated M-CSF and frequently observed in TT carriers. Our data suggest that genetic variants near CSF1 are associated with AOSD and the rs11102024 T allele links to higher M-CSF levels and systemic outcome. These results provide a promising initiative for the early intervention and therapeutic target of AOSD. Further investigation is needed to have better understandings and the clinical implementation of genetic variants nearby CSF1 in AOSD.